Radiation-termocatalytic processes for hydrogen production from water - Agayev, T.N.; Melikova, S.Z.; Hadzhiyeva, H.F. (Вопросы атомной науки и техники, 2019)
The radiation-thermal-catalytic processes of water decomposition in the n-ZrO₂-n-Al₂O₃+H₂O system are investigated. The kinetics of molecular hydrogen accumulation was studied during radiolytic processes of water decomposition in the systems under study. The values of the accumulation rates and radiation-chemical yields of hydrogen during the radiolysis of water in the n-ZrO₂-n-Al₂O₃+H₂O system at various temperatures have been determined. Besides this, it was shown that the results obtained serve as a base for checking the scenarios of normal and emergency conditions of nuclear reactors refrigerated by water. Досліджено радіаційно-термокаталітичні процеси розкладання води в системі n-ZrO₂-n-Al₂O₃+H₂O. Вивчено кінетику накопичення молекулярного водню при радіолітичних процесах розкладання води в досліджуваних системах. Визначено значення швидкостей накопичення і радіаційно-хімічних виходів водню при радіолізі води в системі n-ZrO₂-n-Al₂O₃+H₂O при різних температурах. Отримані результати можуть бути основою для перегляду сценарію нормальних і аварійних режимів роботи водоохолоджуючих ядерних реакторів. Исследованы радиационно-термокаталитические процессы разложения воды в системе n-ZrO₂-n-Al₂O₃+H₂O. Изучена кинетика накопления молекулярного водорода при радиолитических процессах разложения воды в исследуемых системах. Определены значения скоростей накопления и радиационно-химических выходов водорода при радиолизе воды в системe n-ZrO₂-n-Al₂O₃+H₂O при различных температурах. Полученные результаты могут служить основой для пересмотра сценария нормальных и аварийных режимов работы водоохлаждаемых ядерных реакторов.